A escola e as práticas de poder disciplinar - Nunes, Nei Antonio (Perspectiva, 2000)
This arlicle analyses how some aspects of disciplinary practices act on individual bodies and "souls"and the way they spread throughout society, particulary on disciplinary institutions like schools. The article is based on Michel Foucault Discipline and Punish.